Accuracy of intensity-modulated radiation therapy dose calculations: Verification based on-board conebeam CT imaging - Lalida Tuntipumiamorn (2018)
Background: Patient's conebeam computer tomography (CBCT) images have suggested a possibility for adaptive radiotherapy although the dose delivery is of structural complexity. It is of practical importance to verify and test the intensity-modulated radiation (IMRT) planning system for radiation therapy. Objective: Verify accuracy of dose calculations based on CBCT imaging. Materials and methods: Electron density calibration curve was generated for planning CT and CBCT data set using two CT phantoms (Gammex RMI® and Catphan® 600). Anthropomorphic head and neck phantom images were acquired from planning CT and CBCT. The routine IMRT technique was generated on the planning CT, which was applied to the CBCT. Dose distributions were computed. All LiF TLD-100 dosimeters were calibrated with gamma-ray. Forty-eight TLD measuring points were chosen in five different slices of the phantom. Measurements were repeated four times, and the average dose was compared to the reading doses on both CT and CBCT plans. Dose volume histograms (DVH) of various structures were generated, and dose statistics were analyzed. Results: Hounsfield unit obtained from Catphan phantom was similar between planning CT and CBCT. IMRT dose calculations based on the planning CT and CBCT agreed well with reading doses at 48 points. Statistical point doses by DVH calculation on CBCT were about 3% lower than those by the conventional CT. Dose ratios calculated over measured ones ranged from 0.82 to 1.09. Conclusion: Point doses and DVH calculations based on the planning CT and on-board CBCT were in acceptable agreement. CT phantom specifically designed for CBCT is recommended to improve accuracy of IMRT dose calculation on CBCT images.